Transcatheter and Surgical Aortic Valve Replacement in Patients With Previous Cardiac Surgery: A Meta-Analysis - Li, Yi-ming; Tsauo, Jia-yu; Jia, Kai-yu; Liao, Yan-biao; Xia, Fan; Zhao, Zheng-gang; Chen, Mao; Peng, Yong (Frontiers in Cardiovascular Medicine, 2021)
Background: Many patients who have aortic stenosis and are transcatheter aortic valve replacement (TAVR) candidates have underwent prior cardiac surgery (PCS). The aim of this study was to provide a robust summary comparison between patents with PCS who underwent TAVR versus surgical aortic valve replacement (SAVR). Methods: We conducted a systematic review and meta-analysis of all published articles on PubMed/Medline, Ovid, EMBASE and Scopus from 2002 to 2019. Results: Total of 13 studies were finally included, yielding a total of 23,148 participants. There was no statistical difference with 30-day (odds ratio (OR): 1.02(0.86-1.21)) or 1-year mortality (OR: 1.18(0.86-1.61)) between the two groups. Subgroup analysis revealed that high-risk patients who underwent TAVR with the transapical approach were associated with increased risk of mortality (OR: 1.45(1.00-2.11)). However, those who underwent TAVR with endovascular approach had a comparable outcome with SAVR. Conclusions: Primary outcomes after endovascular TAVR was similar to those with SAVR and superior to transapical TAVR treatment group in patients with PCS.